Toward effective computational archetype for image guided neuro-surgery - Aboaba, Abdulfattah A.; Hameed, Shihab A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Harun, Rahmat O; Rose, Nurzaini (2010)
In recent years, the advantages offered by Image Guided Surgery (IGS)/ Computer Aided Surgery (CAS) to patients and medical professionals during a minimally-invasive surgical operation are overwhelming. Imaging techniques have had immense growth in their sophistication and can provide the surgeon with high quality guidance. This notwithstanding there is still room for improvement in almost all the areas of IGS application and stages such area as computational time which impedes its full deployment in intra-operative surgical interventional, segmentation, registration, visualization, plus IGS application software and instrumentation. This paper presents a model for the attainment of a more effective computational scheme by looking at possible computational improvement at all stages of IGS procedure but focusing on two aspects of IGS relating to intra-operative surgical intervention. If implemented, it will result into fast and better anatomical segmentation and fast computational scheme.